Estimating the Value of Proposal Power - Knight, Brian (American Economic Review, 2005)
This paper investigates the role of proposal power in the allocation of transportation projects across U.S. congressional districts in 1991 and 1998. The evidence supports the key qualitative prediction of legislative bargaining models: members with proposal power – those sitting on the transportation authorization committee – secure more project spending for their districts than do other representatives. Support for the quantitative restrictions on the value of proposal power is more mixed. I then empirically address several alternative models of legislative behavior, including partisan models, informational roles for committees, models with appropriations committees, and theories of committees as preference outliers.